AN IMPLEMENTATION AND COMPARATIVE ANALYSIS OF FUSION TECHNIQUES ON MEDICAL IMAGES - Joshi, M.R; Helonde, Mr. Roshan P (IJRDO -Journal of Computer Science Engineering, 2015)
Image fusion is the technique of merging several images from multi-modal sources with respective complementary information to form a new image, which carries all the common as well as complementary features of individual images. With the recent rapid developments in the domain of imaging technologies, multisensory systems have become a reality in wide fields such as remote sensing, medical imaging, machine vision and the military applications. Image fusion provides an effective way of reducing this increasing volume of information by extracting all the useful information from the source images. Image fusion creates new images that are more suitable for the purposes of human/machine perception, and for further image-processing tasks such as segmentation, object detection or target recognition in applications such as remote sensing and medical imaging. The overall objective is to improve the results by combining DWT with PCA and non-linear enhancement. The proposed algorithm is designed and implemented in MATLAB using image processing toolbox. The comparison has shown that the proposed algorithm provides a significant improvement over the existing fusion techniques.